Epidemiological, clinical, therapeutic and developmental aspects of acute renal failure in children at the Mother-Child University Hospital Center Jeanne Ebori Foundation from 2021 to 2022 - Lembet Mikolo, Aude M.; Koumba Manga, Anna; Midili, Larissa T.; Mintsa-Mi-Nkama, Edmée J.; Mabery Grodet, Adryana M.; Kiba, Live G.; Koumba Maniaga, Raissa; Mboungani, Morgane; Pemba Mihindou, Mireille; Medza M’Ella, Roselyne; Mve Abagha, Regis; Eyi, Carine; et al. (International Journal of Contemporary Pediatrics, 2024)
Background: Acute renal failure (ARF) is a major public health problem. Little is known about its prevalence in children. The aim of this study is to describe the epidemiological aspects of acute renal failure in children at the Mother-Child CHU Jeanne Ebori Foundation (CHUMEFJE) from 2021 to 2022. Methods: This was a retrospective study conducted over 12 months at the CHUMEFJE. All children aged between one month and 18 years with ARF, defined as creatinine clearance <100 ml/min/1.73m2 or hourly diuresis <0.5 ml/kg for more than 6 hours, were included. Data analysis was performed using EPI info 7.2.2. Results: Out of 3202 children, 251 had ARF, i.e. a prevalence of 7.8%. A total of 243 children were included. The mean age was 2.1±3.6 years. The 0-5 age group accounted for 85.6%. Clinical signs were dominated by AEG (88.5%), fever (85.6%) and dehydration (54.7%). ARF was functional (85.2%). The main causes were AEG (56.4%), malaria (26.3%) and urinary tract infection (5%). Eight (8) patients were on haemodialysis. Cure was noted in 63.8% of cases. Death was attributed mainly to the patient’s past history. AEG was the main cause of AKI in the under-5s, and malaria in the 10-15 age group (p<0.001). Conclusion: ARI is a global public health problem. Low socio-economic status and inadequate technical facilities complicate management.